Peningkatan Peran Dokter Umum Dan Bidan Dalam Meningkatkan Kualitas Reproduksi Perempuan - Nurmadilla, Nesyana; Hamsah, M.; Andi Mappaware, Nasrudin; Syahril, Erlin; Nurrahmah Akib, Marlyanti; Fahmi Utami, Dian (Window of Community Dedication Journal, 2021)
The quality of early life for future generations is largely determined by the quality of mother’s reproduction. Reproductive health is an indicator of the quality of women’s reproduction. The condition of reproductive health in Indonesia is currently not as axpected compared to other ASEAN countries. The purpose of this activity was to improve the quality of women’s reproduction by enhancing the role of general practitioners and midwives in providing education and conducting reproductive examinations. The activity was in the form of seminar with participants from future general practitioners and midwives. After participating in this activity, the majority of participants were able to understand about women’s reproductive health comprehensively and were able to choose the right attitude when facing conditions related to women’s reproductive health.